Monitoring socioeconomic impacts of climate-smart agricultural practices at Doyogena and Basona Worena climate-smart landscapes, Ethiopia - Tesfaye, Abonesh; Nigussie, Abebe; Ambaw, Gebermedihin (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
To achieve food security and agricultural development goals, adaptation to climate change and lower emission intensities per output will be necessary. This transformation must be accomplished without depletion of the natural resource base. Climate-smart agriculture (CSA) is an integrated approach to managing landscapes such as cropland, livestock, forests and fisheries that address the interlinked challenges of food security and climate change. CSA aims to simultaneously achieve increased productivity, enhanced resilience and reduced emissions. In Ethiopia, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in East Africa has established two climate-smart landscapes: one in southern Ethiopia in Doyogena district and the second one in central Ethiopia in Basona Worena district. In these sites, locally appropriate CSA practices are being tested and promoted by the European Union and International Fund for Agricultural Development (EU-IFAD) funded project "Building livelihoods and resilience to climate change in East & West Africa" that is supporting large-scale adoption of CSA technologies and practices.